The Effect of Storytelling and Outdoor Learning Methods on Elementary School Students’ Literacy Regarding the Conservation of Sumatran Tiger (Panthera tigris sumatrae) - Nurkasanah, Siti; Restila, Ridha; Saukhan, Ghiandra NS; Fani, Rifia Tiara; Suprayoga, Tito; Pratiwi, Nurfi; Putri, Frilianty; Nurfadila; Hanifah, Zulfa Nur; Namira, Syafira Nihla; Anggraini, Dewi (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2025)
The Sumatran tiger (Panthera tigris sumatrae) is an endemic species native to Indonesia and is currently classified as Critically Endangered (CE). Conservation cannot depend solely on regulations; it requires active societal participation, strengthened by early environmental literacy. This study evaluated the impact of storytelling and outdoor learning on elementary students’ literacy in Riau Province. A one-group pretest–posttest design was conducted among elementary students aged 9–13 years who met the inclusion criteria, recruited from schools surrounding Tesso Nilo National Park, Riau Province. The intervention consisted of storytelling and outdoor learning activities. Data were obtained using a 12-item questionnaire and analyzed with descriptive statistics and paired t-tests to assess differences in literacy scores before and after the intervention. A total of 71 students participated in the study. The mean pretest score was 59.27 ± 14.08, which increased to 75.80 ± 16.79 on the posttest. A paired t-test confirmed a statistically significant improvement in conservation literacy following the intervention (t = –8.45, df = 70, p < 0.001). This finding suggests that storytelling, combined with outdoor learning, is an effective strategy for enhancing elementary school students' literacy in Sumatran tiger conservation. Storytelling and outdoor learning are effective educational strategies for improving conservation literacy among elementary school students. Early integration of environmental education into school curricula may play a crucial role in fostering long-term commitment to wildlife conservation.